Implementation of Corporate Social Responsibility in Community-Based Sustainable Tourism at Sari Ater Hot Springs Ciater Subang - Annisa Primanty; Evi Novianti; Kasno Pamungkas (Universitas Hamzanwadi, 2024)
Corporate Social Responsibility (CSR) serves as a platform supporting the development of sustainable tourism by involving the environment, local communities, and indigenous wisdom. the implementation of CSR in the tourism industry in West Java has not been optimal. CSR programs are often perceived as mere charitable activities without considering their effectiveness and benefits for the local community. Therefore, the aim of this research is to explore how corporate social responsibility (CSR) is practiced to realize community-based sustainable tourism with Sari Ater Hot Springs Ciater as the research object. The research method employs a qualitative approach with a case study methodology, utilizing observation, interviews, documentation, and literature review. This research is conducted at Sari Ater Hot Springs Ciater, West Java. The results indicate that PT. Sari Ater implements various forms of CSR that enable local communities to fully participate in the operational aspects of the tourist area and directly benefit from it. CSR implementation that focuses on community development can serve as a best model/inspiration in achieving sustainable tourism. Sari Ater Hot Springs Ciater provides an example of how tourism companies can positively influence the environment, local communities, and create a sustainable tourism experience.